2003
DOI: 10.1111/j.1467-842x.2003.tb00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of obesity with anxiety, depression and emotional well‐being: a community survey

Abstract: Objective:To investigate the association of obesity with anxiety, depression and emotional well‐being (positive and negative affect) in three age groups. Methods:A cross‐sectional survey was carried out in Canberra and the neighbouring town of Queanbeyan, Australia, with a random sample from the electoral roll of 2,280 persons aged 20–24, 2,334 aged 40–44, and 2,305 aged 60–64. Results:Self‐reported height and weight were used to classify participants as underweight (body mass index of less than 18.5), accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
180
4
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(210 citation statements)
references
References 21 publications
17
180
4
9
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15] Moreover, our results agree with the earlier studies in that the mental disorder status or its association with BMI levels varies by gender. 7,20,28,29,40 However, our results differed from those of several other studies that have reported no relationship 26 or an inverse association of overweight/obesity with mental disorders in men. [27][28][29] This could be explained by the differences in study population, measurements for psychiatric disorders or potential confounding variables included in the analyses in these studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15] Moreover, our results agree with the earlier studies in that the mental disorder status or its association with BMI levels varies by gender. 7,20,28,29,40 However, our results differed from those of several other studies that have reported no relationship 26 or an inverse association of overweight/obesity with mental disorders in men. [27][28][29] This could be explained by the differences in study population, measurements for psychiatric disorders or potential confounding variables included in the analyses in these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, in the study by Lawlor et al 27 , those with diagnosed mental illnesses over the follow-up period but without a need for hospitalization were not included as cases in the analysis. Another study conducted by Jorm et al 40 also reported that women who were underweight were more likely to have depression or lower emotional well-being, whereas the overweight and obese women tended to have better mental health than women with a normal BMI after controlling for potential confounding factors (including physical illnesses, lack of physical activity, poorer social support, less education and financial problems). However, this study was conducted in people aged 20À64 years from an Australian community with a small sample size (n ¼ 6919), which may partially explain the inconsistent results of this study with those of ours.…”
Section: Discussionmentioning
confidence: 95%
“…1,2,8 For example, the depression-obesity relationship appears to be dependent on sex with the association being positive in women but negative in men. [10][11][12][13] Findings such as these suggest the benefits of invoking a moderator-mediator framework.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence to the contrary notwithstanding, [1][2][3][4][5] an increasing number of reports based on population samples in the United States (US) and elsewhere suggests that, among women, obesity raises the risk of psychopathology at both the sub-clinical [6][7][8][9][10] and clinical [11][12][13] levels. Because it is commonly assumed that obesity engenders mental distress, conclusions drawn from such cross-sectional findings typically attribute higher depression/anxiety symptom levels or disorder rates to elevated relative body weight (weight adjusted for height or body mass index (BMI)).…”
Section: Introductionmentioning
confidence: 99%